Association Between Intimate Partner Violence and Breastfeeding Duration: Results From the 2004-2014 Pregnancy Risk Assessment Monitoring System. (May 2018) - Wallenborn, Jordyn T.; Cha, Susan; Masho, Saba W.
Background: Intimate partner violence is a major public health problem that disproportionately affects women. Current literature investigating the relationship between intimate partner violence and breastfeeding is inconsistent. Research aim: This study aims to investigate the relationship between physical intimate partner violence that occurs in the preconception or prenatal period and any breastfeeding duration. Methods: Data from the retrospective, cross-sectional 2004-2014 Pregnancy Risk Assessment Monitoring System were analyzed ( N = 195, 264). The outcome, breastfeeding duration, was categorized as never breastfed, breastfed 8 weeks or less, and breastfeed more than 8 weeks. Multinomial logistic regression was used to obtain crude and adjusted odds ratios and 95% confidence intervals. Results: Approximately 6% ( n = 11, 766) of survey respondents reported preconception and/or prenatal intimate partner violence, and 36.3% ( n = 67, 667) of women reported never breastfeeding. The odds of discontinuing breastfeeding before 8 weeks were 18% higher among women who reported experiencing abuse 12 months before pregnancy compared with women who did not report intimate partner violence (adjusted odds ratio = 1.18; 95% confidence interval [1.01, 1.37]). All other estimates showed an overlapping 95% confidence interval. Conclusion: Breastfeeding is essential in improving maternal and child health; however, women in abusive relationships may face additional barriers to breastfeeding. Further research is needed to better understand the impact of violence on breastfeeding behaviors to inform healthcare practices and interventions.